HIV pre-exposure prophylaxis and incidence of sexually transmitted infections in Brazil, 2018 to 2022: An ecological study of PrEP administration, syphilis, and socioeconomic indicators. - Paula Knoch Mendonça Gil; Danilo Dos Santos Conrado; Ana Isabel do Nascimento; Micael Viana de Azevedo; João Cesar Pereira da Cunha; Gabriel Serrano Ramires Koch; Camila Guadeluppe Maciel; Alisson André Ribeiro; Antonio Conceição Paranhos Filho; Márcio José de Medeiros; Cláudia Du Bocage Santos-Pinto; Everton Falcão de Oliveira (Public Library of Science (PLoS), 2023)
Background Human immunodeficiency virus (HIV) pre-exposure prophylaxis (PrEP) is one of the pillars of a combination prevention strategy for reducing the risk of new infections caused by HIV. The daily use of antiretroviral drugs by individuals who are not infected with HIV is required to prevent infection. Although its efficacy has been well established in the literature, in recent years, the decreased supply of antiretroviral drugs has been associated with an increase in the incidence of sexually transmitted infections (STI) and changes in the social determinants of health. An ecological study was conducted covering a five-year period (2018-2022), starting from the year of initiation of PrEP administration in Brazilian state capitals. Principal findings Descriptive analysis was performed, and the spatial distribution of study data was taken into account. Correlation analysis was used to assess the association between PrEP administration, the incidence and detection rate of STI, and socioeconomic data. The southern region showed the highest incidence rates of STI, but the northern and northeastern regions demonstrated the worst socioeconomic indicators, especially those related to illiteracy and basic sanitation. PrEP administration was significantly correlated with illiteracy (ρ = -0.658), per capita income (ρ = 0.622), public garbage collection (ρ = 0.612), syphilis (ρ = 0.628) and viral hepatitis (ρ = 0.419) incidences. Further, all STI were significantly associated with illiteracy and per capita income. Significance Our findings highlight the need to continue exploring PrEP use and rising syphilis rates. In terms of policy, PrEP administration appears to be inversely associated with regions of greater social vulnerability. Further efforts should focus on the social determinants and health needs of this population to improve access to PrEP and reduce social disparities.